Factores de riesgo para infección por escherichia coli productor de betalactamasas de espectro extendido en adultos hospitalizados del complejo hospitalario San Pablo - Ruíz Rodríguez, Randolph (2014)
To demonstrate that old age, long hospital stay, use of invasive procedures, prior use of antibiotics and comorbidity are risk factors for infection by extended-spectrum beta-lactamases (ESBL) producing Escherichia coli of hospitalized adults from San Pablo Hospital Complex. Methods. This paper is a case-control study. Through random systematic selection and pairing we obtained a sample of representative cases and controls groups for the three main clinics of the San Pablo Hospital Complex (CHSP). The information of the variables was obtained from Laboratory and Statistics services, and through review of medical records. Univariate analysis was performed in the first instance, and the odds ratios were obtained for each condition. The Chi -square test was performed and 95% confidence intervals (CI) were prepared to determine whether each condition was significant. Later, multivariate analysis was performed using binary logistic regression for variables with p < 0.1 in univariate analysis. Finally, we considered statistical significance at p < 0.05. Results. A total of 54 cases and 56 controls were included. At univariate analysis, four risk factors were significant : old age (OR = 3.5 , CI 1.4 to 8.9 , p < 0.01) , long hospital stay ( OR = 5.0 , CI = 1.5 to 16.2 , p < 0.01 ), prior use of antibiotics (OR = 5.3 , CI = 1.9 to 14.4 , p < 0.001) and comorbidity (OR = 2.3 CI = 1.1-5.1 , p < 0.05). At multivariate analysis old age (p = 0.01) and previous use of antibiotics ( p < 0.01) were significant. Conclusions. Old age and previous use of antibiotics are risk factors for infection with ESBL -producing E. coli in adult hospitalized patients of CHSP